Perbaikan Retensi Air dengan Aplikasi Bahan Organik pada Pertanaman Sorgum - Nurmi Nurmi; Nikmah Musa; Zulzain Ilahude (Jurnal Ilmu Pertanian Indonesia, 2024)
This study aimed to determine the role of water hyacinth (Eichhornia crassipes Mart.) organic matter on water retention at pF 2.54 and pF 4.2, available water content, and bulk density (BD). The research method used was a factorial randomized block design. The first factor was the sorghum variety, which consisted of 2 levels, namely, V1 (variety) and V2 (Kawali). The second factor was the dose of water hyacinth organic matter, which consisted of 5 levels, namely P0 (without the application of water hyacinth organic matter), P1 (10 tons.ha-1), P2 (20 tons.ha-1), P3 (30 tons.ha-1), and P4 (40 tons.ha-1). Water retention was measured at pF 2.54 and pF 4.2 using a pressure plate apparatus and pressure membrane apparatus, respectively, and BD was measured using the ring method. The results showed that the treatment of organic matter application and varieties had a significant effect on water retention at pF 2.54, available water content, and BD with the best treatment of 40 tons of organic matter application and Kawali variety, but not affecting water retention at pF 4.2. There was no interaction between water hyacinth organic matter and sorghum varieties to improve water retention and BD. The highest water retention at pF 2.54 was 32.24% (P4), and the highest available water content was 11.67% (P4) but not significantly different from P3 (11.55%); the lowest BD was 1.11 g.cm-3 (P4) but not significantly different from P3 (1.13 g.cm-3). A very strong positive linear and negative linear correlation exists between available water content and BD with plant height, panicle length, and sorghum yield. Keywords: bulk density, water hyacinth, water content, water retention, sorghum